Penataan Lingkungan Desa Berbasis Eco-Friendly Melalui Daur Ulang Galon Plastik Bekas Dan Optimalisasi Taman Hatinya PKK di Desa Trasan, Kecamatan Juwiring, Kabupaten Klaten - Muhamad Fadli; Acika Febianti Zaura; Brillian Toriq Alhussna; Hayyina Mazida; Nita Jeanis Virnanda; Najuwa Ilham; Tazqia Aqiatus Zahra; Mutia Nur Janah; Alya Citra Ramadhani Rahayu; Desi Putri Budi Permata Hati; Zainal 'Arifin (Abdimas Indonesian Journal, 2026)
The growing volume of plastic waste remains a pressing environmental concern in rural areas, while the Family Welfare Movement (PKK) Garden in Trasan Village has not been optimally utilized as a means of greening and yard-land management through the cultivation of family medicinal plants (TOGA) and vegetables. This condition became the background for a community service (KKN) program that adopted an eco-friendly concept through the reuse of discarded plastic gallon containers and the optimization of the PKK Garden in Trasan Village, Juwiring District, Klaten Regency. The program began with field observation, coordination with the village government and the PKK Mobilization Team, collection of used plastic gallons, construction of gates from recycled materials, and reorganization of the PKK Garden, all carried out participatively with the involvement of the community and PKK cadres. The results show that reusing plastic gallons reduced plastic waste while producing gates that enhanced the village environment, while the reorganized PKK Garden became better organized and functioned as a green space for TOGA and vegetable cultivation. The program also raised public awareness of environmental management and strengthened collaboration among students, the village government, and the community, and is expected to serve as a model of eco-friendly village environmental management that can be replicated in other villages facing similar conditions.